Heritability of Platelet Responsiveness to Aspirin in Activation Pathways Directly and Indirectly Related to Cyclooxygenase-1 - Faraday, Nauder; Yanek, Lisa R.; Mathias, Rasika; Herrera-Galeano, J. Enrique; Vaidya, Dhananjay; Moy, Taryn F.; Fallin, M. Daniele; Wilson, Alexander F.; Bray, Paul F.; Becker, Lewis C.; Becker, Diane M. (Circulation (New York, N.Y.), 2007)
Background— The inability of aspirin (acetylsalicylic acid [ASA]) to adequately suppress platelet function is associated with future risk of myocardial infarction, stroke, and cardiovascular death. Genetic variation is a proposed but unproved mechanism for insufficient ASA responsiveness. Methods and Results— We examined platelet ASA responsiveness in 1880 asymptomatic subjects (mean age, 44±13 years; 58% women) recruited from 309 white and 208 black families with premature coronary heart disease. Ex vivo platelet function was determined before and after ingestion of ASA (81 mg/d for 2 weeks) with the use of a panel of measures that assessed platelet activation in pathways directly and indirectly related to cyclooxygenase-1, the enzyme inhibited by ASA. The proportion of phenotypic variance related to CHD risk factor covariates was determined by multivariable regression. Heritability of phenotypes was determined with the use of variance components models unadjusted and adjusted for covariates. ASA inhibited arachidonic acid–induced aggregation and thromboxane B 2 production by ≥99% ( P <0.0001). Inhibition of urinary thromboxane excretion and platelet activation in pathways indirectly related to cyclooxygenase-1 was less pronounced and more variable (inhibition of 0% to 100%). Measured covariates contributed modestly to variability in ASA response phenotypes ( r 2 =0.001 to 0.133). Phenotypes indirectly related to cyclooxygenase-1 were strongly and consistently heritable across races (h 2 =0.266 to 0.762; P <0.01), but direct cyclooxygenase-1 phenotypes were not. Conclusions— Heritable factors contribute prominently to variability in residual platelet function after ASA exposure. These data suggest a genetic basis for the adequacy of platelet suppression by ASA and potentially for differences in the clinical efficacy of ASA.